Relationship of Location, Price, and Promotion to Interest in Buying Gordyn at Soni Interior House - Dedy Lazuardi; Ihdina Gustina; Muammar Rinaldi (Institute of Computer Science (IOCS), 2022)
This study aims to determine the relationship between Buying Interest Location at Soni Interior House, knowing the relationship to Buying Interest at Soni Interior House, knowing the relationship to Buying Interest at Soni Interior House, and knowing the relationship to Buying Interest at Soni Interior House House. The research methodology used is the descriptive quantitative method. The type of data used in this study is quantitative data, namely data obtained in the form of numbers or numbers. Sources of data in the form of primary data and secondary data. Primary data was obtained from the results of distributing questionnaires to shops that made purchases at the Promotion of Soni Interior House, secondary data was obtained from data and literature relating to the problems discussed. The research population that will be used in the study are all consumers who use the services of the company during the period 2016 to 2020 as many as 55,648 consumers. By using the Slovin formula with an error rate of 10%, the number of samples obtained is 100 respondents. Data were analyzed using the multiple linear regression analysis methods. The results of the analysis show that the location has a positive and significant relationship with buying interest in Soni Interior House.